2014
DOI: 10.1111/2041-210x.12301
|View full text |Cite
|
Sign up to set email alerts
|

Nondestructive estimates of above‐ground biomass using terrestrial laser scanning

Abstract: Summary1. Allometric equations are currently used to estimate above-ground biomass (AGB) based on the indirect relationship with tree parameters. Terrestrial laser scanning (TLS) can measure the canopy structure in 3D with high detail. In this study, we develop an approach to estimate AGB from TLS data, which does not need any prior information about allometry. We compare these estimates against destructively harvested AGB estimates and AGB derived from allometric equations. We also evaluate tree parameters, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
671
8
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 544 publications
(711 citation statements)
references
References 28 publications
29
671
8
3
Order By: Relevance
“…We agree that such an effect cannot be completely ruled out, and it is probably all the more significant that trees ≥ 10 Mg represent only 3 % of the reference data set of Chave et al (2014). Collecting more field data on large trees should therefore constitute a priority if we are to improve multi-specific, broad-scale allometric models, and the recent development of nondestructive AGB estimation methods based on terrestrial lidar data should help in this regard (e.g., Calders et al, 2015). However, regardless of whether the nonlinear increase in crown mass ratio with tree mass held to a sampling artifact, we have shown that it was the source of systematic error in the reference model that used a unique geometric approximation with an average form factor for all trees.…”
Section: Crown Mass Ratio and The Reference Biomass Model Errormentioning
confidence: 99%
“…We agree that such an effect cannot be completely ruled out, and it is probably all the more significant that trees ≥ 10 Mg represent only 3 % of the reference data set of Chave et al (2014). Collecting more field data on large trees should therefore constitute a priority if we are to improve multi-specific, broad-scale allometric models, and the recent development of nondestructive AGB estimation methods based on terrestrial lidar data should help in this regard (e.g., Calders et al, 2015). However, regardless of whether the nonlinear increase in crown mass ratio with tree mass held to a sampling artifact, we have shown that it was the source of systematic error in the reference model that used a unique geometric approximation with an average form factor for all trees.…”
Section: Crown Mass Ratio and The Reference Biomass Model Errormentioning
confidence: 99%
“…Despite being a relatively new field, TLS allows a rapid acquisition of 3-D data with various applications [20][21][22][23]. Similar to Lidar, TLS represents a non-destructive method of obtaining biomass estimates, however, unlike Lidar, which covers large areas, TLS data capture is restricted to only a few meters [24,25]. Given its ability to acquire data on the ground, it can be used for validation of other remote sensing datasets [17,19].…”
Section: Introductionmentioning
confidence: 99%
“…Because of its high level of detail and accuracy, TLS has the potential to estimate in a standardized and automatic way tree diameters, tree height, tree volume, and thus tree biomass Hosoi et al 2013). This technology may constitute a great alternative to biomass destructive measurements and may improve considerably the local biomass estimates (Calders et al 2014). The analysis of such three-dimensional large datasets is still in progress, but several ongoing methodological developments should make this technology useful soon.…”
Section: Light Detection and Ranging Systemsmentioning
confidence: 99%
“…Here, we show that some new technologies, such as terrestrial LiDAR or stereo-photogrammetry may be a promising way to improve significantly tree volume or biomass estimation without any destructive measurement. For instance, large trees that contribute a large fraction of the overall forest biomass (Chave et al 2003) are difficult to measure through destructive sampling (Picard et al 2012), and terrestrial LiDAR could make the volume measurement easier (Calders et al 2014).…”
Section: Very High-resolution Optical Imagerymentioning
confidence: 99%